Case Report: Postmenopausal hyperandrogenism misled by adrenal incidentaloma: a rare case of androgen-secreting ovarian adult granulosa cell tumor and clinical implications - Cao, Conghui; Wang, Xiaoli (Frontiers in Oncology, 2026)
BackgroundOvarian adult-type granulosa cell tumors (AGCTs) are rare sex cord-stromal neoplasms, accounting for 95% of ovarian granulosa cell tumors (GCTs) but only 10% of which secrete androgens. For postmenopausal women, hyperandrogenism is commonly attributed to conditions like polycystic ovary syndrome (PCOS), while androgen-secreting AGCTs are extremely rare, often leading to diagnostic challenges—especially when accompanied by adrenal incidentalomas that may divert clinical attention.Case presentationThis study presents a case of a 57-year-old postmenopausal Chinese woman (menopause at 48) with 5 years of progressive hyperandrogenic symptoms (facial/perianal/leg hirsutism, vertex/frontal alopecia, deepened voice, clitoral hypertrophy). Initial evaluation revealed a left adrenal nodule and elevated testosterone; however, pelvic ultrasound (limited by bowel gas) showed no obvious abnormalities in the ovaries. Further tests at the First Affiliated Hospital of China Medical University confirmed markedly elevated serum testosterone (37.00 nmol/L, ref: 0.69-1.49 nmol/L) and free testosterone (300.90 pmol/L, ref: 0.77-33.03 pmol/L), suppressed LH/FSH, low AMH (0.01 ng/mL), and a 2.6×2.0 cm enhancing nodule in the right adnexa on pelvic MRI. Notably, adrenal-derived androgens were within normal ranges in this case, ruling out adrenal origin of hyperandrogenism. She underwent laparoscopic total hysterectomy + bilateral salpingo-oophorectomy; permanent pathological examination (with immunohistochemistry: Vimentin+, α-inhibin+, Calretinin+, Ki67+ ~2%) confirmed FIGO Stage IA AGCT (frozen section initially suggested benign tissue). Postoperatively, her androgen levels normalized, hirsutism/oily skin/acne improved, blood pressure decreased, though voice deepening persisted.DiscussionThis case underscores critical clinical lessons: Postmenopausal women with severe hyperandrogenism require comprehensive adrenal and pelvic evaluation (prioritizing MRI over ultrasound due to higher sensitivity for small tumors) even with adrenal findings. Comprehensive hormonal profiling (testosterone, adrenal androgens, gonadotropins, AMH) aids in distinguishing tumorous from non-tumorous causes, and permanent pathology is essential to avoid misdiagnosis from frozen sections. Surgical resection (bilateral salpingo-oophorectomy for postmenopausal patients) is effective for AGCT management, and long-term follow-up is crucial given the risk of late recurrence. Additionally, AGCT diagnosis is feasible in institutions without inhibin B/genetic testing via integrated clinical, hormonal, and imaging data. This case aims to raise awareness of rare androgen-secreting AGCTs to reduce diagnostic delays and improve management.